Pertumbuhan dan Hasil Kopi Grafting Robusta/Liberika pada Klon dan Waktu Pemupukan yang berbeda - Kurniawan, Hari; Evizal, Rusdi; Septiana, Liska Mutiara; Rini, Maria Viva (JURNAL AGROTROPIKA, 2022)
Grafting of different coffee species (interspecific grafting) aims to take advantage of the superiority of the rootstock and promote the growth and production of the scion. For example, Robusta coffee is grafted with Liberika coffee as rootstock. One of the principles of fertilization is the application of fertilizer at the right time. This study aimed to determine the effect of clones of Robusta/Liberica interspecific grafting and different fertilization times on the growth and yield of Robusta coffee. The research was conducted in a 15-year-old coffee plantation with the rootstock of Liberika coffee of the Red Robinson variety which was grafted to the scion of multiclonal Robusta coffee. Planting distance of coffee was 2.5 m x 2.5 m and shade trees were Gliricidia sepium. This research used a split plot design arranged in a factorial (4x2) with three replications so that there were 24 experimental units. The main plot was the time of fertilization, namely in early April and October and in early May and November. As sub-plots, there were Robusta coffee clones, namely Korolla 1, Korolla 2, Tugu Bungkuk, and Darmani. The results showed that fertilization time, clones, and their interactions did not affect the number of primary branches, primary branch length, number of secondary branches, fruit weight of harvested samples, number of fruit per bunch, fruit weight per bunch, dry seed weight per bunch, and coffee yield per tree. The interaction of coffee clones and fertilization time had a significant effect on the number of pods per branch, the number of harvested samples, dry bean weight of harvested samples, dry bean weight per branch, and coffee yield per hectare. For Darmani coffee clones, delaying fertilization from April and October to May and November reduced coffee yield. Key words : Interspesific grafting, Liberica, Robusta, time of fertilization, yield